THE EIGHTH GRADE STUDENTS’ SATISFACTIONS ON THE ENGLISH TEACHER PROFESSIONALISM IN TEACHING ENGLISH AS FOREIGN LANGUAGE AT SMP NEGERI 8 SINGARAJA IN ACADEMIC YEAR 2018/2019 - L. Sari; Sudirman Sudirman; L.D.S Adnyani (Universitas Pendidikan Ganesha, 2019)
This research aimed to know the eighth grade students’ satisfaction on the English teacher professionalism in teaching English as Foreign Language at SMP Negeri 8 Singaraja in academic year 2018/2019. The object of this research was English teacher professionalism. The subject of this research was 151 eighth grade students’ satisfaction at SMP Negeri 8 Singaraja. The data of this research were obtained by using questionnaire and interview question sheet to the students. This research was used mixed-method approach because the writer combines both quantitative and qualitative method in analyzing the data. This result indicate that average score from reliability,responsiveness,empathy,guarantee and physical evidence which get an average score of 3.9, 3.89, 4.1, 4.1, and 4.1 that means all of variables are in the satisfying level. Finally, it can be concluded that students are showing positive respond against english teacher professionalism in English learning